Microcontroller-Based Switching for Cost-Effective Load Management and Industrial Automation - Karuppusamy, P. (Journal of Electrical Engineering and Automation, 2024)
This study proposes a microcontroller-based switching system designed for cost-effective load management and industrial automation. Using a microcontroller such as Arduino or PIC, this system controls relay modules to manage various electrical loads efficiently. Real-time data from current and temperature sensors enable accurate load management, preventing overloads and improving power usage. The system automates load switching based on predefined schedules and real-time conditions, reducing energy consumption and operational costs. Safety is enhanced through overcurrent and temperature protection mechanisms, safeguarding equipment, and ensuring safe operations. Additionally, optional communication modules allow for remote monitoring and control, facilitating timely adjustments and interventions. This comprehensive approach to load management and automation proposes significant cost savings, improved efficiency, and improved safety and reliability in industrial settings.